Conflict Perspectives in Analyzing and Understanding Organizational Behavior - Mohd Nain, Ahmad Shukry (Universiti Teknologi Malaysia, 2004)
Complex organizations and highly structured organizational networks are part of the obvious features of contemporary life. Organizations, being universal and worldwide phenomenon are becoming increasingly crucial to our life; they often serve as a means for our social, economic and political development. In our contemporary life, organization have developed to be very complex and diverse entities, formed with very high structure of networks. As a result of these developments, theories have been developed in an attempt to have a better understanding of organizations and thus creating a more effective and efficient organizations. The rational model has been projected as a gigantic and fabulous instrument and way of thinking towards the contemporary organizations, whereby an organization is perceived and believed to be a stable entity, always integrated, consensus, ordering and well coordinated, only if the rules of the scientific management and bureaucratic model are being fully adopted. Nevertheless, in early 1970s, Western cultures have reached a discontinuity. The decade opened opportunities and led to a societal confusion that we now recognize as signaling the end of an era, the end of a millennia, the ends of the cold war and sovereign states. The changes were massive, they affected the meaning of power. They affected our values. As a 'result, theories were developed to explain the changes that happened in the recent decades or predict the events of coming decades. However, rationality models were increasingly recognized to be devoid of empirical content. Whilst, order and progress in organization had not happened all the time, cooperation was too fragile and fleeting, purposiveness was too elusive, conflict and coercion were too frequent, disintegration, differences, antagonism and divided loyalties were valid representations of contemporary organizational reality, which was demonstrated by a huge number of institutions in contemporary Western civilization. Thus, this article is an attempt to analyze conflict as a significant intellectual paradigm and approach in understanding organizational behavior.